Polymeric fiber reinforced concrete exposed to fire - Dias, Dainer Marçal; Calmon, João Luiz; Vieira, Geilma Lima (Revista ALCONPAT, 2019)
The aim of this work was to investigate the influence of the addition of polypropylene, polyester, polyamide, aramid and aramid pulp fibers on the behavior of concretes subjected to high temperatures. For that, test specimens with fiber additions were made at a rate of 2 kg/m3 and submitted to temperatures in furnace, as well as to high temperatures through direct fire test. Columns were also built and subjected to a live fire simulator belonging to the Espírito Santo Fire Department - Brazil. Microstructural and mechanical properties were analyzed. It has been observed that the fibers may influence the properties of the concrete and that fire tests with standard fire load may be an alternative or complementary analysis of concrete subjected to elevated temperatures.